Computational Algebra, Coding Theory, and Cryptography: Theory and Applications - Hashem Bordbar (Axioms)
The primary aim of this Special Issue is to explore innovative encoding and decoding procedures that leverage various algebraic structures to enhance error-control coding techniques [...]